Ointment formulation of snakehead fish (Channa striata) Extract with variations of CMC-Na and carbopol - Mohamad Andrie; Wintari Taurina (Universitas Ahmad Dahlan, 2021)
Â Snakehead fish (Channa striata) and kelulut honey (Trigona sp.) have the potential to accelerate the wound-healing process. These natural ingredients are formulated in the form of ointment because ointment is an external medicine that is easy to apply and has long contact with the skin. Previous research has shown that the snakehead fish extract ointment undergoes phase separation, so it needs a material that can bind the snakehead fish extract and kelulut honey as the active substances in the preparation. This study aimed to determine the effect of variations in the concentration of CMC-Na (3%, 4.5%, 6%) and Carbopol (0.5%, 1%, 2%) as a binder on the ointment physical properties and to determine the best snakehead fish (Channa striata) extract ointment formulation. The ointment of snakehead fish extract was tested for organoleptic, homogeneity, spreadability, and adhesion. The test results were analyzed by One Way ANOVA with a confidence level of 95%. The results showed that the higher the concentrations of CMC-Na and Carbopol used, the greater the adhesive power and the lower the spreadability. Ointment with Carbopol has a wider spreadability and a softer consistency than ointment with CMC-Na. The best formulation is shown by the Carbopol 0.5% (F4) formula, where the average spreadability with a load of 150 g is 5.09 cm and the average adhesion is 229 seconds.